(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The women dalits with Indian hats always live in peace. They kept silent about their rights, their rights, their rights and their barbarism against them. They have no knowledge of their own body, their own benefits, and their own life. The cross-border articulation of brutality, treatment and abuse against them is manifested in types of envy, hunger, disease, physical and mental torment, aggression Ignorance, disorders, unemployment, work and barbaric therapy. The global forces of feudalism, caste and people in human society have their lives only for a fall. The fundamental part of the mind lives in the most troublesome conditions. In this age and era of innovation and post-innovation, it still turned into a phase of malice.